The rise of Warcraft. - Mastrapa, Gus.; Rignall, Jaz.
Bizzard's MMO has gone from a humble real-time strategy series to the most dominant MMO in gaming. GamePro delves into the history of its transformation and the reasons for World of Warcrafts staggering success.
Keywords: WarCraft; World of Warcraft; Multi-user dungeons; Massively multiplayer online (MMO) games